Experience involving the implementation and compliance with the ERAS® at a small gynecologic oncology centre: Izkušnje z uvajanjem in skladnostjo delovanja z ERAS® protokolom v majhnem ginekološkem onkološkem centru - Pakiž, Maja; Lonzarič, Nives; Krebs, Bojan; Dobnik, Sarah; Sobočan, Monika; Zadravec, Kristina (Acta Medico-Biotechnica, 2021)
Purpose: We report on the first patient with refractory hypoxemia treated with venovenous extracorporeal membrane oxygenation (VV ECMO) at the Medical Intensive Care Unit of the University Medical Centre Maribor. Case report: A 52-year-old male was admitted after successful cardiopulmonary resuscitation from out-of-hospital cardiac arrest (first rhythm was ventricular fibrillation, with 40 min to return of spontaneous circulation). The patient underwent primary percutaneous revascularization of the left anterior descending coronary artery with insertion of one coronary stent. Hypoxemia was present during patient transportation and the procedure and continued to worsen after admission. Due to refractory hypoxemia caused by aspiration pneumonia, treatment with the VV ECMO was initiated. The ECMO procedure was performed without complications and led to improvement in gas exchange and lung mechanics. The patient was then successfully weaned from ECMO, decannulated, and extubated. After extubation, the patient’s course of treatment was complicated by hospital pneumonia and catheter-related blood stream infection. As his state deteriorated, reintubation was necessary. Despite intensive treatment, the patient died on day 30. Conclusions: Response to the VV ECMO treatment of refractory hypoxemia due to aspiration pneumonia was positive and without complications. In spite of initial improvement, the patient died after several weeks due to recurring infection and septic shock.